Dielectric Spectroscopy of Polyimide Films Treated by Nanosecond High Voltage Pulsed Driven Electrical Discharges in Water. Issue 2 (13th June 2015) - Miron, Camelia; Zhuang, Jie; Sava, Ion; Kruth, Angela; Weltmann, Klaus‐Dieter; Kolb, Juergen F.
Abstract : Dielectric properties of aromatic polyimide films treated by nanosecond pulsed electrical discharges generated in distilled water were evaluated with respect to permittivity and its dependency on discharge time. The relative permittivity of the polyimide films decreased after treatment by water plasma. The largest decrease was observed after a short discharge time, from a value of 3.6 for the untreated sample to 1.92 for the 10 min plasma treated samples. XRD analysis has shown a slight increase of the degree of intermolecular ordering and stronger π–π interactions during plasma treatment over shorter periods of time. However, the distance between the chains was also increasing, giving rise to an increased free volume. This effect may be responsible for the decrease of the relative permittivity of the polymer film. Abstract : Aromatic polyimide films are treated by nanosecond pulse electrical discharges generated in distilled water. Impedance spectroscopy is employed for the measurement of dielectric constants before and after treatment of polyimide samples in water plasma. The relative permittivity of the polymer films decreases after plasma treatment, a remarkably low value of ɛ = 1.92 at 1 MHz being obtained for the polyimide samples after 10 min of plasma exposure.